القصدية في الخطاب الدّعوي عبد الرّزاق البدرخطيب الحرم المدني أنموذجاً - زعبوب محمد العربي (My University, 2026)
Summary: It becomes evident, through the analysis of the sermons of “ Abd al-Razaq al-badr, that the principale of intentionality constitutes a central axis in the construction a his dawa-oriented, discourse.his purposes are directed toward achieving guidance and exerting both emotional and behavioral influence on the audience, through a conscious employment of religious texts and their connection to real-life contexts. Intentionality is manifested in the clarity of purpose, the coherence of the argumentative structure, and the careful selection of effective rhetorical strategies that combine persuasion and engagement. It also reflects his attentiveness to the condition and level of the addresse, which enhances the effectiveness of the discourse and enables it to fulfill its reformative amis. ----------------------- ملخّص: يتّضح منّ خلال تحّليل خطابات عبد الرزّاق البدر، أنّ مبدأ القصديّة يُمثّل محوراً أساسياً في بناء خطابه الدّعوي، إذّ تتّجه مقاصده إلى تحقيق الهداية والتأثير الوجداني والسّلوكي في المتلقي، عبّر توظيف واع للنصوص الشرعيّة وربطها بسياقات الواقع. وقدّ تجلّت القصديّة في وضوح الغاية وترابط البنيّة الحجاجيّة، وانتقاء الأساليب المؤثرة التي تجمع بين الإقناع والإمتاع، كما يُظهر حرصه على مراعاة حال المخاطب ومستواه، ممّا يُعزّز فاعليّة الخطاب ويُحقق مقاصده الإصلاحيّة، وعليه فإنّ خطاب البدر يُعّد أنموذجاً تطبيقياً بارزاً لتجسيد القصديّة في الخطاب الإسلامي المعاصر، بما يخدم وظيفة الإبلاغ والتوجيه، وفق رؤية علميّة رصينة . ------------------ Résumé: L'analyse des prèches d'abd al-razzaq al-badr montre que le principe d'intentionnalité constitue un axe fondamental dans la construction de son discours religieux. Ses sermons visent à réaliser la guidance, à exercer une influence affective et comportementale sur le public, à travers une utilisation pertinente des textes religieux. l'intentionnalité se manifeste également dans la clarté des obJectifs ,la cohérence de la structure argumentative et le choix de procédés persuasifs combinant conviction. Ainsi ,les prèches d'al-badr représentent un modèle significatif de l'application de l'intentionnalité dans le discours islamique de l'orientation et de la réforme.
Keywords: القصدية، الخطاب الدعوي، التداولية، عبد الرزاق البدر، الحجاج، الاقناع، التواصل الاسلامي، المقاصد الإصلاحية